Business intelligence capability: the effect of top management and the mediating roles of user participation and analytical decision making orientation - Kulkarni, Uday R. (2017)
In this study, we draw on the structurational model of technology in an institutional setting to investigate how top management affects the development of a firm’s business intelligence (BI) capability. We propose a multiple mediator model in which organizational factors, such as user participation and analytical decision making orientation, act as mediating mechanisms that transmit the positive effects of top management championship to advance a firm’s BI capability. BI capability has two distinct aspects: information capability and BI system capability. Drawing on data collected from 486 firms from six different countries, we found support for the mediating effects of top management championship through user participation and analytical decision making orientation. These findings contribute to a nuanced understanding of how firms can develop BI capability. This study is one of the first to comprehensively investigate the antecedents of BI capability.